Educational Model as an Important Factor Influencing on Conjugation Between Higher Education and Labor Sphere - V. S. Senashenko; E. P. Struchkova (Высшее образование в России, 2019)
The article presents the results of the analysis of possible mechanisms of conjugation between the higher education sphere and labor market in the context of various educational models. The liberal, professional and mixed educational models are used for the identification of optimal conditions for conjugation between the higher education system and labor sphere. In addition, these educational models are used for detection of essential differences in the educational system’s response to the requirement of compliance of educational standards to professional standards. The analysis of these components of the considered educational models has revealed the additional requirements. The implementation of these requirements is necessary for the formation of more effective mechanisms, which allow for educational management and conjugation of the higher education system with the labor sphere. It is shown that the erroneous identification of the educational model is associated with certain risks. These risks include the discrepancy between the choice of the educational model and the priorities of the state educational policy; underestimation of the influence of the features of the economic structure of the country and the mechanisms of the labor sphere formation on the higher education system; overstatement of the possibilities of the educational model for the successful solution of the problems of accessibility, quality and efficiency of higher education. The discrepancy between the choice of the definite educational model and the current educational reality can generate destructive trends in the system of higher education.